2013
DOI: 10.4236/mrc.2013.24019
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO and NO on Ceria- and Pt-Supported TiO<sub>2</sub>: <i>In Situ</i> FTIR Study

Abstract: Pt/TiO 2 , Ce/TiO 2 and binary system PtCe/TiO 2 catalysts were prepared by impregnation method and the structural properties of these catalysts were investigated by means of XRD, CO-TPD and UV-vis diffuse reflectance spectroscopy. As investigated by XRD, the composition of the prepared samples anatase and rutile phases with higher amount of anatase phase and its particle size was in the range of 19 -22 nm. The band gap also decreased from 3.1 to 2.85 after addition of metal to TiO 2 . The adsorption and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…12b). Moreover, two new peaks at 2181 and 2210 cm −1 (assigned to β-type Ti 4+ -CO and α-type Ti 4+ -CO species) [18] appear, but the peak at 2296 cm −1 (attributed to the Ti 4+ -NO − ) disappears with the introduction of UV light. However, the formed Pt-NCO species (2200 cm −1 )…”
Section: Catalytic Performancesmentioning
confidence: 94%
See 3 more Smart Citations
“…12b). Moreover, two new peaks at 2181 and 2210 cm −1 (assigned to β-type Ti 4+ -CO and α-type Ti 4+ -CO species) [18] appear, but the peak at 2296 cm −1 (attributed to the Ti 4+ -NO − ) disappears with the introduction of UV light. However, the formed Pt-NCO species (2200 cm −1 )…”
Section: Catalytic Performancesmentioning
confidence: 94%
“…17 With the introduction of UV light (curve B in Fig. 11b), the increased peak of Pt 0 -CO shifts to a low wavenumber (from 2079 to 2076 cm −1 ), and is further split into a new absorption peak at about 2050 cm −1 which may be attributed to the Pt-CO-Pt [18]. Moreover, the intensity of CO 2 at peak of 2346 cm −1 is significantly increased, indicating that UV irradiation promote the oxidation of CO at Pt sites even in the absence of O 2 .…”
Section: Catalytic Performancesmentioning
confidence: 97%
See 2 more Smart Citations
“…Important peculiarities of CeO 2 are its high oxygen storage capacity and easy reducibility [05]. There are many studies of the nature of the species formed during interaction of NO x with ceria [05, 17,[19][20][21][22][23][24][25][26][27][28][29][30][31] and ceria-containing systems [05, 16,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and the proposed structures are summarized in Table 1. Based on the paper of Niwa et al [21] and a more recent work of Martinez-Arias et al [20], several authors reported formation of various species, such as NO - [16,19,20,[32][33][34]48], cis-and trans-hyponitrites [16,19,20,…”
Section: Introductionmentioning
confidence: 99%